Chub (Leuciscus cephalus) as a bioindicator of contamination of the Vltava River by synthetic musk fragrances - Hájková, K; Pulkrabová, J; Hajslová, J; Randák, T; Zlábek, V (Archives of environmental contamination and toxicology, 2007)
Synthetic musk fragrances, which are contained in almost all scented consumer products, enter aquatic environment mainly by way of wastewater paths. To monitor contamination of the Vltava River by these relatively persistent chemicals in the surroundings of Prague industrialized agglomeration, chub (Leuciscus cephalus) was employed as a bioindicator. Validated gas chromatography-mass spectrometry method was used for fish sample examination. Polycyclic musks, represented by 1,3,4,6,7,8-hexahydro-4,6,6,7,8,8-hexamethyl-cyclopenta-(gamma)-2-benzopyran (galaxolide) and 1-(5,6,7,8-tetrahydro-3,5,5,6,8,8-hexamethyl-2-naphthalenyl)-ethanone (tonalide) were the most abundant representatives of this group; their levels in fillets were in the range of 1.7 to 105.9 microg/kg and 0.9 to 19.3 microg/kg wet weight, respectively. Nitro-musks, musk ketone, and musk xylene were also detected in most samples; nevertheless, their levels were lower, <or=2 microg/kg. Significant contamination of resident fish was recognised in the locality of Klecany, which is located 6 km downstream from a large municipal sewage-treatment plant (STP). High levels of musks found in the locality of Vranany, 32 km downstream from Prague STP, were caused not only by this emission source but probably also by the effluents from the local plant that produces cleaning agents in Velvary.
Keywords: parfém; Cyprinidae; chemické látky znečišťující vodu; Fatty Acids, Monounsaturated; řeky; Gas Chromatography-Mass Spectrometry; ekosystém; kyseliny mastné mononenasycené; Environmental Monitoring; plynová chromatografie s hmotnostně spektrometrickou detekcí; Water Pollutants, Chemical; Ecosystem; Animals; Perfume; Rivers; monitorování životního prostředí; zvířata